Induction of Melanogenesis by Fosfomycin in B16F10 Cells Through the Upregulation of P-JNK and P-p38 Signaling Pathways - Sana Ullah; You Chul Chung; Chang-Gu Hyun (Antibiotics, 2020)
Fosfomycin disodium salt (FDS), which is a water-soluble extract, is a bactericidal drug used to inhibit the synthesis of cells. Moreover, it has been found to be effective in the treatment of urinary tract infections. The present study was conducted to investigate the melanogenesis-stimulating effect of FDS in B16F10 cells. Several experiments were performed on B16F10 cells: the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, the melanin content assay, the cellular tyrosinase activity assay, and Western blotting. FDS upregulated the activity of tyrosinase in a dose-dependent manner at a wide concentration range of 0–1 mg/mL, which showed no cytotoxicity. It also increased the melanin content and the activity of the microphthalmia-associated transcription factor (MITF), tyrosinase related protein 1 (TRP-1), and tyrosinase related protein 2 (TRP-2) enzymes in a dose-dependent manner. Western blotting results showed that FDS clearly upregulated the phosphorylation of c-Jun N-terminal kinases (JNK) and p38 pathways. These data are clear evidence of the melanogenesis-inducing effect of FDS in B16F10 murine melanoma cells.